O Jogo Musical COBRA (1984) de John Zorn: reflexões sobre sua história e prática - Felipe Jose Oliveira Abreu (2013)
The main goal of this research is to describe the operation and the learning process of the game piece Cobra, an experimental and open composition using free improvisation, developed by John Zorn in 1984. By conducting two practical assemblies in the course of two years, Ive got into the piece under different approaches, encompassing its improvisational, compositional and performatic potentials. The game uses cards and signs among the musicians to articulate series of improvisational systems, each one with its own rules. Emerging from interactions/relationships between musicians, each version of the game is unique and can have any length or instrumentation, always being a collective creation. The dissertation describes this learning process critically, including a brief historical approach of improvisation (chapter 1) and of Zorns compositional trajectory and his game pieces (chapter 2), followed by a detailed description of the piece Cobra and by reflexions raised by its practical assembly.